4a zeolite and a method for producing the same

CN122897418APending Publication Date: 2026-10-13ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611105802.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]依据本申请的一个或多个实施例提供一种4A沸石及其制备方法,解决了传统4A沸石钙离子交换能力较差及静态水吸附容量较低的技术问题

Benefits of technology

本申请的4A沸石的制备方法,采用SiO2/Al2O3摩尔比低于 2(具体为1.5~1.9)的铝过量凝胶体系,引入富余铝源,同时适度提升体系碱性, Na2O/SiO2摩尔比为1.5~2.0,促进铝源(铝酸钠溶液)解离为四羟基铝酸根,同时高碱环境可稳定液相富余四羟基铝酸根,避免过量铝团聚生成堵塞孔道的氢氧化铝沉淀或方钠石杂晶,使其以高分散形态的非骨架羟基铝(Al-OH)附着于晶粒表面,形成大量带负电铝羟基位点,从而增加了4A沸石整体的负电荷密度,并提供了额外的钙离子吸附位点,高负电荷密度带来更强静电吸附作用力,从而提高了4A沸石的钙离子交换能力和静态水吸附容量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897418A_ABST
    Figure CN122897418A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of 4A zeolite, comprising the following steps: mixing a sodium aluminate solution and a water glass solution to form a first slurry; sequentially performing static aging and segmented crystallization on the first slurry to obtain a second slurry; and sequentially performing solid-liquid separation, washing and drying on the second slurry to obtain the 4A zeolite; wherein in the first slurry, the molar ratio of SiO2 and Al2O3 is 1.5-1.9, the molar ratio of Na2O and SiO2 is 1.5-2.0, and the molar ratio of H2O and Al2O3 is 120-180.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of zeolite molecular sieve technology, and in particular to a 4A zeolite and its preparation method. Background Technology

[0002] 4A zeolite molecular sieves are widely used in detergent additives, PVC stabilizers, and drying and purifying adsorbents due to their excellent ion exchange and selective adsorption capabilities. 4A zeolite molecular sieves are also essential raw materials for the preparation of 3A and 5A molecular sieves, further expanding their application areas. 4A zeolite molecular sieves have become the most widely used synthetic zeolite molecular sieve.

[0003] Currently, the theoretical value of the framework silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of traditional 4A zeolite molecular sieves is 2.00. However, the calcium ion exchange capacity of this type of molecular sieve is not high, and the static water adsorption capacity is not large, which limits its application in water softening treatment and gas adsorption drying, separation and purification. Summary of the Invention

[0004] According to one or more embodiments of this application, a 4A zeolite and its preparation method are provided, which solves the technical problems of poor calcium ion exchange capacity and low static water adsorption capacity of traditional 4A zeolite.

[0005] A first aspect of this application provides a method for preparing 4A zeolite, comprising the following steps: slurrying a sodium aluminate solution and a water glass solution to obtain a first slurry; subjecting the first slurry to static aging and segmental crystallization sequentially to obtain a second slurry; and subjecting the second slurry to solid-liquid separation, washing, and drying sequentially to obtain the 4A zeolite; wherein, in the first slurry, the molar ratio of SiO2 to Al2O3 is 1.5~1.9, the molar ratio of Na2O to SiO2 is 1.5~2.0, and the molar ratio of H2O to Al2O3 is 120~180.

[0006] Optionally, the mass concentration of Al2O3 in the sodium aluminate solution is 35 g / L to 50 g / L; and / or, the caustic ratio αk of the sodium aluminate solution is 1.4 to 1.6.

[0007] Optionally, the mass concentration of SiO2 in the water glass solution is 360 g / L to 378 g / L; and / or, the water glass modulus M of the water glass solution is 3.0 to 3.1.

[0008] Optionally, the temperature for pulping and gelling is 35℃~55℃, and the time for pulping and gelling is 30min~60min.

[0009] Optionally, the static aging temperature is 35℃~55℃, and the static aging time is 30min~90min.

[0010] Optionally, the segmented crystallization includes: A guiding agent is added to the first slurry after static aging to carry out the first crystallization, and an initial crystallized slurry is obtained. The initial crystallized slurry is subjected to a second crystallization to obtain a second slurry.

[0011] Optionally, the amount of the guiding agent added is 0.001% to 0.01% of the volume of the first slurry; and / or, The first crystallization temperature is 65℃~80℃, and the first crystallization time is 3h~6h; and / or, The second crystallization temperature is 92℃~98℃, and the second crystallization time is 2h~5h.

[0012] Optionally, the washing step continues until the pH of the final filtrate is 10-11.

[0013] A second aspect of this application provides a 4A zeolite, which is prepared by the preparation method described in the first aspect.

[0014] Optionally, the 4A zeolite satisfies at least one of the following properties (1) to (4): (1) The particle size D50 of the 4A zeolite is 2μm to 5μm; (2) The calcium ion exchange capacity of the 4A zeolite is ≥310mg / g; (3) The static water adsorption capacity of the 4A zeolite is ≥ 27.5%; (4) The molar ratio of SiO2 to Al2O3 in the 4A zeolite is 1.50 to 1.90.

[0015] Compared with the prior art, the technical solution provided in this application has the following beneficial effects: The preparation method of 4A zeolite in this application adopts an aluminum excess gel system with a SiO2 / Al2O3 molar ratio of less than 2 (specifically 1.5~1.9), introduces an excess aluminum source, and appropriately increases the alkalinity of the system. The Na2O / SiO2 molar ratio is 1.5~2.0, which promotes the dissociation of the aluminum source (sodium aluminate solution) into tetrahydroxyaluminate. At the same time, the high alkalinity environment can stabilize the excess tetrahydroxyaluminate in the liquid phase, avoid the agglomeration of excess aluminum to form aluminum hydroxide precipitates or sodalite impurities that block the pores, and allow it to attach to the surface of the grains in a highly dispersed form of non-framework aluminum hydroxyl (Al-OH), forming a large number of negatively charged aluminum hydroxyl sites. This increases the overall negative charge density of 4A zeolite and provides additional calcium ion adsorption sites. The high negative charge density brings stronger electrostatic adsorption force, thereby improving the calcium ion exchange capacity and static water adsorption capacity of 4A zeolite.

[0016] The 4A zeolite prepared by the method of this application has a uniform and concentrated particle size distribution and a small D50 (2μm~5μm). Fluorescence analysis shows that its bulk total silica-alumina ratio (the molar ratio of SiO2 / Al2O3) is 1.50~1.90, which has higher calcium exchange capacity and adsorption capacity. The calcium ion exchange capacity reaches more than 310mg / g, and the static water adsorption capacity is ≥27.5%. It can meet the requirements of 4A zeolite for softening water with high hardness and high adsorption capacity application scenarios. Attached Figure Description

[0017] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and disclosure, and together with the description serve to explain the principles of this application and disclosure.

[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a schematic flowchart of a method for preparing 4A zeolite according to some embodiments of this application; Figure 2 Scanning electron microscope image of 4A zeolite prepared in Example 1 of this application. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0021] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. The term "implementation" as used herein has a similar understanding.

[0022] In this application, except where expressly stated, any matters or issues not mentioned are directly applicable to those known in the art without any modification. Furthermore, any implementation described in this application can be freely combined with one or more other implementations described in this application, and the resulting technical solutions or concepts shall be considered part of the original disclosure or original record of this application, and should not be regarded as new content not disclosed or anticipated in this application, unless those skilled in the art consider the combination to be clearly unreasonable.

[0023] Any method steps, processes, and operations described in this application should not be construed as necessarily requiring them to be performed in a particular order as discussed or shown, unless explicitly specified. It should also be understood that additional or alternative steps may be used unless otherwise stated.

[0024] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0025] Any specific numerical values ​​disclosed herein (including the endpoints of numerical ranges) are not limited to their exact values, but should be understood to also include values ​​close to the exact value, such as all possible values ​​within ±5% of the exact value. Furthermore, with respect to the disclosed numerical ranges, one or more new numerical ranges can be obtained by arbitrarily combining the endpoint values ​​of the range, the endpoint values ​​with specific point values ​​within the range, and the specific point values ​​themselves; these new numerical ranges should also be considered as specifically disclosed herein.

[0026] Unless otherwise stated, the terms used herein have the same meaning as commonly understood by those skilled in the art, and if a term is defined herein and its definition differs from the common understanding in the art, the definition herein shall prevail.

[0027] First aspect Please see Figure 1 This application provides a method for preparing 4A zeolite through some embodiments, including the following steps: S1, Sodium aluminate solution and water glass solution are slurried to form a gel to obtain the first slurry. In the first slurry, the molar ratio of SiO2 to Al2O3 is 1.5~1.9, the molar ratio of Na2O to SiO2 is 1.5~2.0, and the molar ratio of H2O to Al2O3 is 120~180. S2, the first slurry is subjected to static aging and segmented crystallization in sequence to obtain the second slurry; S3, the second slurry is subjected to solid-liquid separation, washing and drying in sequence to obtain 4A zeolite; The preparation method of 4A zeolite in the above embodiments of this application adopts an aluminum excess gel system with a SiO2 / Al2O3 molar ratio of less than 2 (specifically 1.5~1.9), introduces an excess aluminum source, and at the same time moderately increases the alkalinity of the system, with a Na2O / SiO2 molar ratio of 1.5~2.0, to promote the dissociation of the aluminum source (sodium aluminate solution) into tetrahydroxyaluminate. At the same time, the high alkalinity environment can stabilize the excess tetrahydroxyaluminate in the liquid phase, avoid the agglomeration of excess aluminum to form aluminum hydroxide precipitates or sodalite impurities that block the pores, and allow it to attach to the surface of the grains in a highly dispersed non-framework aluminum hydroxyl (Al-OH) form, forming a large number of negatively charged aluminum hydroxyl sites, thereby increasing the overall negative charge density of 4A zeolite and providing additional calcium ion adsorption sites. The high negative charge density brings stronger electrostatic adsorption force, thereby improving the calcium ion exchange capacity and static water adsorption capacity of 4A zeolite.

[0028] For example, the molar ratio of SiO2 to Al2O3 can be 1.5, 1.6, 1.7, 1.8, or 1.9. Within this range, the molar ratio of SiO2 to Al2O3 provides a suitable surplus aluminum source. Too much or too little surplus aluminum source is not conducive to the formation of stable Al4A zeolite with a large number of negatively charged aluminum hydroxyl sites.

[0029] In some preferred embodiments, the molar ratio of SiO2 to Al2O3 is 1.7 to 1.8.

[0030] For example, the molar ratio of Na2O to SiO2 can be 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0. Within this range, the system exhibits moderate alkalinity.

[0031] In some preferred embodiments, the molar ratio of Na2O to SiO2 is 1.6 to 1.8.

[0032] For example, the molar ratio of H2O to Al2O3 can be 120, 130, 140, 150, 160, 170, or 180. In some preferred embodiments, the molar ratio of H2O to Al2O3 is 140 to 160.

[0033] In some embodiments, the mass concentration of Al2O3 in the sodium aluminate solution is 35 g / L to 50 g / L. This Al2O3 mass concentration ensures sufficient aluminum source for zeolite synthesis and the formation of an aluminum-excess gel system during the reaction. Simultaneously, the sodium aluminate solution with an Al2O3 mass concentration of 35 g / L to 50 g / L exhibits good fluidity, facilitating uniform mixing and transport during the reaction. Examples of Al2O3 mass concentrations in the sodium aluminate solution include 35 g / L, 37 g / L, 39 g / L, 41 g / L, 43 g / L, 45 g / L, 47 g / L, and 50 g / L.

[0034] αk is an expression for the molar ratio of aluminum oxide (Al₂O₃) to sodium oxide (Na₂O) in a sodium aluminate solution, reflecting the compositional characteristics of the solution. In some embodiments, the caustic ratio αk of the sodium aluminate solution is 1.4–1.6. In the embodiments of this application, using a sodium aluminate solution with an αk value of 1.4–1.6 as the aluminum source can relatively reduce the amount of sodium oxide used, because a lower αk value means a relatively higher mass concentration of aluminum oxide in the solution, which helps to reduce raw material costs and waste generation, conforming to the principles of green chemistry. On the other hand, sodium aluminate solutions with an αk value between 1.4 and 1.6 have suitable alkalinity, which further facilitates the formation of stable aluminosilicate structures during zeolite synthesis. Exemplarily, the αk of the sodium aluminate solution can be 1.4, 1.45, 1.5, 1.55, 1.6, etc.

[0035] In some embodiments, the mass concentration of SiO2 in the water glass solution is 360 g / L to 378 g / L. This SiO2 mass concentration range ensures sufficient silicon source participation in zeolite synthesis and the formation of an aluminum-excess gel system during the reaction. Simultaneously, the water glass solution with a SiO2 mass concentration of 360 g / L to 378 g / L exhibits good fluidity, facilitating uniform mixing and transport during the reaction. For example, the SiO2 mass concentration in the water glass solution can be 360 ​​g / L, 363 g / L, 366 g / L, 369 g / L, 372 g / L, 375 g / L, 378 g / L, etc.

[0036] The modulus M of water glass represents the molar ratio of silicon dioxide (SiO2) to sodium oxide (Na2O) in water glass, i.e., M = SiO2 / Na2O. The modulus of water glass affects its viscosity, setting time, strength, and other properties. Generally, a higher modulus results in higher viscosity, longer setting time, but also increased strength. In the embodiments of this application, the modulus M of water glass is between 3.0 and 3.1, which facilitates gel formation while maintaining a molar ratio of Na2O to SiO2 of 1.5 to 2.0 in the first slurry. For example, the modulus M of the water glass solution can be 3.0, 3.02, 3.04, 3.06, 3.08, 3.1, etc.

[0037] In some embodiments, the temperature for pulping and gelling is 35°C to 55°C, and the time for pulping and gelling is 30 min to 60 min.

[0038] The process of slurry formation specifically refers to adding sodium aluminate solution and water glass solution to a synthesis tank under stirring and mixing them to allow the two solutions to react fully and form the first slurry, laying the foundation for subsequent steps (such as static aging and segmented crystallization).

[0039] The slurry-gelling temperature range of 35℃ to 55℃ and the slurry-gelling time range of 30 min to 60 min are conducive to the thorough mixing and uniform dispersion of sodium aluminate solution and water glass solution. This ensures that the components in the reaction system can be uniformly contacted, laying a good foundation for subsequent segmental crystallization. On the other hand, the slurry-gelling temperature range of 35℃ to 55℃ can accelerate the chemical reaction between raw materials, promoting the initial formation of the 4A zeolite aluminosilicate structure. This helps to shorten the entire zeolite preparation cycle, improve production efficiency, and reduce energy consumption. The slurry-gelling stage is the initial stage of zeolite grain growth. By controlling the temperature and time, the nucleation and growth rate of grains can be regulated, thereby affecting the final zeolite grain size and distribution. A temperature range of 35℃ to 55℃ and a time range of 30 min to 60 min are conducive to the formation of 4A zeolite with uniform particle size distribution and small grains. For example, the temperature for pulping and gelling can be 35℃, 37℃, 39℃, 41℃, 43℃, 45℃, 47℃, 49℃, 51℃, 53℃, 55℃, etc.; the time for pulping and gelling can be 30min, 35min, 40min, 45min, 50min, 550min, 60min, etc.

[0040] In some implementations, the static aging temperature is 35°C to 55°C, and the static aging time is 30 min to 90 min.

[0041] Static aging refers to the aging process of a uniformly mixed slurry (first slurry) in a static state for a period of time during zeolite synthesis. The purpose of this step is to allow the components in the slurry to react and blend more fully, creating favorable conditions for the subsequent crystallization process.

[0042] Static aging stabilizes the aluminosilicate structure in the first slurry, promoting zeolite crystal growth and development during subsequent crystallization. Furthermore, under suitable static aging temperatures (35℃~55℃) and times (30min~90min), the aluminosilicate structure in the first slurry is further adjusted and optimized, facilitating uniform seed crystal formation and distribution. This lays the foundation for uniform zeolite grain growth in the subsequent process. For example, static aging temperatures can be 35℃, 37℃, 39℃, 41℃, 43℃, 45℃, 47℃, 49℃, 51℃, 53℃, 55℃, etc.; and static aging times can be 30min, 40min, 50min, 60min, 70min, 80min, 90min, etc.

[0043] In some implementations, segmented crystallization includes: A guiding agent was added to the first slurry after static aging to carry out the first crystallization, resulting in the initial crystallized slurry. The initial crystallized slurry is subjected to a second crystallization to obtain a second slurry.

[0044] In some embodiments, the amount of the directing agent added is 0.001% to 0.01% of the volume of the first slurry.

[0045] The molar ratio of Na2O, Al2O3, SiO2, and H2O in the directing agent can be (12–16):1:(9–10):(240–480). The directing agent, acting as a "template" or "guide" for grain growth, is added at 0.001%–0.01% of the first slurry volume. It induces 4A zeolite grains to grow along a specific direction, resulting in a more regular and ordered grain structure. This helps to further improve the adsorption performance and mechanical strength of the zeolite. By precisely controlling the amount of directing agent added, the pore structure and pore size distribution of the zeolite can be fine-tuned to better suit the performance of the target molecules. Furthermore, the volume of the directing agent being 0.001%–0.01% of the total volume of the first slurry helps to reduce the agglomeration of zeolite grains during growth, resulting in a more uniform grain distribution. For example, the volume of the guiding agent can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, etc., of the total volume of the first slurry.

[0046] In some embodiments, the temperature of the first crystallization is 65°C to 80°C, and the time of the first crystallization is 3 hours to 6 hours.

[0047] Under suitable initial crystallization temperatures (65℃~80℃) and times (3h~6h), zeolite grains can grow sufficiently to form 4A zeolite with high crystallinity, which helps to further enhance the calcium ion exchange capacity and adsorption capacity of the zeolite. During the initial crystallization process, by precisely controlling the temperature and time, the introduction of impurity ions and the formation of lattice defects can be reduced, thereby improving the purity of 4A zeolite. For example, the initial crystallization temperature can be 68℃, 69℃, 70℃, 72℃, 74℃, 76℃, 78℃, 80℃, etc.; the initial crystallization time can be 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, etc.

[0048] In some embodiments, the temperature of the second crystallization is 92°C to 98°C, and the time of the second crystallization is 2 hours to 5 hours.

[0049] At higher secondary crystallization temperatures (92℃~98℃) and appropriate crystallization times (4h~8h), zeolite grains can further refine their internal structure and increase crystallinity. This helps enhance the stability and durability of zeolite, enabling it to maintain excellent performance even under harsh environments such as high temperature, high pressure, or chemical corrosion. During the secondary crystallization process, cations (such as sodium ions) in the zeolite lattice have the opportunity to undergo more complete exchange and rearrangement, thereby further improving the ion exchange capacity of zeolite.

[0050] For example, the temperature of the second crystallization can be 92℃, 93℃, 94℃, 95℃, 96℃, 97℃, 98℃, etc.; the time of the second crystallization can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, etc.

[0051] In some embodiments, the washing step is performed until the pH of the final filtrate is 10 to 11.

[0052] During zeolite synthesis and crystallization, some unreacted raw materials, byproducts, or impurity ions may remain. Washing and controlling the pH of the final filtrate at 10–11 can effectively remove these residues, improving the purity of the zeolite. During washing, controlling the pH of the filtrate allows for fine-tuning of the zeolite surface charge state and hydrophilicity / hydrophobicity, further enhancing the calcium ion exchange capacity and static water adsorption capacity of the zeolite. Furthermore, the washing process helps remove residues from the zeolite pores, reducing pore blockage and thus increasing the porosity and specific surface area of ​​the zeolite, thereby further improving its calcium ion exchange capacity and static water adsorption capacity.

[0053] Second aspect Some embodiments of this application provide a 4A zeolite, which is prepared by the preparation method described in the first aspect.

[0054] In some embodiments, the particle size D50 of 4A zeolite is 2 μm to 5 μm.

[0055] In some embodiments, the calcium ion exchange capacity of 4A zeolite is ≥310 mg / g; In some embodiments, the static water adsorption capacity of 4A zeolite is ≥ 27.5%; In some embodiments, the molar ratio of SiO2 to Al2O3 in 4A zeolite is 1.50 to 1.90. This molar ratio of SiO2 to Al2O3 in 4A zeolite refers to the total silicon-aluminum ratio (molar ratio of SiO2 to Al2O3) in the bulk phase of 4A zeolite, including silicon and aluminum in the framework and in the non-framework.

[0056] Particle size D50 refers to the particle size value corresponding to a cumulative distribution percentage of 50%, also known as the median diameter or median particle size. 4A zeolite with a particle size D50 of 2μm to 5μm has a small particle size and a large specific surface area, enabling the exchange of Na... + Sufficient exposure improves the utilization rate of the original intrinsic ion exchange centers, which can further enhance the calcium ion exchange capacity of 4A zeolite. For example, the particle size D50 of 4A zeolite is 2μm, 2.2μm, 2.768μm, 3.289μm, 3.532μm, 4.267μm, 4.714μm, etc.

[0057] Calcium ion exchange capacity, also known as calcium ion exchange capacity, is usually measured in mg / g, which is the number of milligrams of calcium carbonate exchanged per gram of zeolite. In this application, the calcium ion exchange capacity of the zeolite was determined using the static exchange method specified in industry standard HG / T 2524. Specifically, at 25℃, 0.5g of dried zeolite sample was placed in 100mL of calcium chloride standard solution (concentration 0.025 mol / L, pH=11.0), magnetically stirred for 30min, and then filtered. The concentration of remaining calcium ions in the filtrate was determined by EDTA complexometric titration. The calcium ion exchange capacity (Q, mg / g) was calculated using the following formula: Q = [(C0- C1) × V ×100.09] / m Where: C0 is the initial calcium ion concentration (mol / L), C1 is the calcium ion concentration after exchange (mol / L), V is the solution volume (L), 100.09 is the molar mass of CaCO3 (g / mol), and m is the dry basis mass of the zeolite (g). The calcium ion exchange capacity of the 4A zeolite in this application is significantly improved compared with that of traditional 4A zeolite (around 280 mg / g), which is of great significance to the field of softening technology for water with high hardness.

[0058] Static water adsorption capacity refers to the weight of water completely adsorbed by a molecular sieve per unit weight when the sieve reaches equilibrium adsorption under certain temperature and gas pressure. A static water adsorption capacity ≥27.5% directly reflects the excellent adsorption capacity of 4A zeolite. High adsorption capacity means that under the same conditions, zeolite can adsorb more water or target molecules, which has significant advantages for applications such as drying, dehumidification, and gas separation.

[0059] Based on the above performance characteristics, the 4A zeolite prepared in this application is particularly suitable for applications in water softening treatment and gas adsorption drying, separation and purification. Especially for applications with high water hardness and high adsorption capacity, the 4A zeolite prepared in this application can meet the needs of these scenarios for high-performance adsorption materials.

[0060] Example To better understand this application, the following description, in conjunction with embodiments, further illustrates this application. However, the scope of protection claimed in this application is not limited to the scope of the embodiments.

[0061] In the following examples, unless otherwise specified, all experimental instruments and raw material components and quantities involved are commercially available products or can be prepared by known methods. Experimental methods not specifying specific conditions in the examples are generally determined according to national / industry standards; if no corresponding national / industry standard exists, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed. Unless otherwise specified, the specific parameters used in each step of the material preparation process in each example and comparative example are the same.

[0062] Example 1 According to the feed formula, the molar ratio of SiO2 / Al2O3 is 1.5, the molar ratio of Na2O / SiO2 is 1.6, and the molar ratio of H2O / Al2O3 is 130. Sodium aluminate solution and water glass solution are measured and added to the synthesis tank under stirring to form a slurry and gel, thus obtaining the first slurry. The gelation temperature is set at 35℃, and the mixture is stirred for 60 minutes. Stirring is then stopped for static aging at 37℃ for 80 minutes. Stirring is then turned on again, and a directing agent is added at 0.01% of the volume of the first slurry. High-temperature steam is introduced to raise the temperature for the first stage of crystallization at 65℃ for 6 hours. High-temperature steam is introduced again to raise the temperature for the second stage of crystallization at 98℃ for 3 hours, thus obtaining the second slurry. The second slurry is then subjected to solid-liquid separation, washing, and drying to obtain 4A zeolite.

[0063] The particle size (D50) of the 4A zeolite, measured by laser particle size analyzer, was 2.768 μm. Fluorescence analysis showed a SiO2 / Al2O3 molar ratio of 1.55, a saturated sodium chloride water vapor adsorption capacity of 27.8% at 35℃, and a calcium ion exchange capacity of 327 mg / g. A scanning electron microscope image of the 4A zeolite is shown below. Figure 2 As shown, Figure 2 The results show that the 4A zeolite has a uniform particle size distribution.

[0064] Example 2 According to the feed formula, the molar ratio of SiO2 / Al2O3 is 1.9, the molar ratio of Na2O / SiO2 is 1.8, and the molar ratio of H2O / Al2O3 is 180. Sodium aluminate solution and water glass solution are measured and added to the synthesis tank under stirring to form a slurry and gel, thus obtaining the first slurry. The gelation temperature is set at 45℃, and the mixture is stirred for 40 minutes. Stirring is then stopped for static aging at 45℃ for 60 minutes. Stirring is then turned on again, and a directing agent is added at 0.001% of the volume of the first slurry. High-temperature steam is introduced to raise the temperature for the first stage of crystallization at 75℃ for 3.5 hours. High-temperature steam is introduced again for the second stage of crystallization at 98℃ for 3.5 hours, thus obtaining the second slurry. The second slurry is then subjected to solid-liquid separation, washing, and drying to obtain 4A zeolite.

[0065] The particle size D50 of the 4A zeolite was measured to be 4.267 μm by a laser particle size analyzer. The molar ratio of SiO2 / Al2O3 in the fluorescence analysis was 1.90. The adsorption capacity of saturated sodium chloride water vapor at 35℃ was 27.6%, and the calcium ion exchange capacity was 315 mg / g.

[0066] Example 3 According to the feed formula, the molar ratio of SiO2 / Al2O3 is 1.7, the molar ratio of Na2O / SiO2 is 1.6, and the molar ratio of H2O / Al2O3 is 160. Sodium aluminate solution and water glass solution are measured and added to the synthesis tank under stirring to form a slurry and gel, thus obtaining the first slurry. The gelation temperature is set at 40℃, and the mixture is stirred for 50 minutes. Stirring is then stopped for static aging at 42℃ for 60 minutes. Stirring is then turned on again, and a guiding agent is added at 0.01% of the volume of the first slurry. High-temperature steam is introduced to raise the temperature for the first stage of crystallization at 70℃ for 3 hours. High-temperature steam is introduced again to raise the temperature for the second stage of crystallization at 95℃ for 4 hours, thus obtaining the second slurry. The second slurry is then subjected to solid-liquid separation, washing, and drying to obtain 4A zeolite.

[0067] The particle size D50 of the 4A zeolite was measured to be 3.532 μm by a laser particle size analyzer. The molar ratio of SiO2 / Al2O3 in the fluorescence analysis was 1.68. The adsorption capacity of saturated sodium chloride water vapor at 35℃ was 27.9%, and the calcium ion exchange capacity was 321 mg / g.

[0068] Example 4 According to the feed formula, the molar ratio of SiO2 / Al2O3 is 1.8, the molar ratio of Na2O / SiO2 is 1.5, and the molar ratio of H2O / Al2O3 is 140. Sodium aluminate solution and water glass solution are measured and added to the synthesis tank under stirring to form a slurry and gel, thus obtaining the first slurry. The gelation temperature is set at 48℃, and the mixture is stirred for 30 minutes. After stirring, static aging is carried out at 52℃ for 40 minutes. Stirring is then turned on, and without the addition of a directing agent, high-temperature steam is introduced to raise the temperature of the aged first slurry for a first-stage crystallization at 80℃ for 4 hours. High-temperature steam is introduced again to raise the temperature for a second-stage crystallization at 92℃ for 5 hours, thus obtaining the second slurry. The second slurry is then subjected to solid-liquid separation, washing, and drying to obtain 4A zeolite.

[0069] The particle size D50 of the 4A zeolite was measured to be 4.714 μm by a laser particle size analyzer. The molar ratio of SiO2 / Al2O3 in the fluorescence analysis was 1.83. The adsorption capacity of saturated sodium chloride water vapor at 35℃ was 27.5%, and the calcium ion exchange capacity was 313 mg / g.

[0070] Example 5 According to the feed formula, the molar ratio of SiO2 / Al2O3 is 1.6, the molar ratio of Na2O / SiO2 is 1.9, and the molar ratio of H2O / Al2O3 is 150. Sodium aluminate solution and water glass solution are measured and added to the synthesis tank under stirring to form a slurry and gel, thus obtaining the first slurry. The gelation temperature is set at 55℃, and the mixture is stirred for 40 minutes. Stirring is then stopped for static aging at 55℃ for 30 minutes. Stirring is then turned on again, and a directing agent is added at 0.001% of the volume of the first slurry. High-temperature steam is introduced to raise the temperature for the first stage of crystallization at 80℃ for 3 hours. High-temperature steam is introduced again to raise the temperature for the second stage of crystallization at 98℃ for 3 hours, thus obtaining the second slurry. The second slurry is then subjected to solid-liquid separation, washing, and drying to obtain 4A zeolite.

[0071] The particle size D50 of the 4A zeolite was measured to be 3.289 μm by a laser particle size analyzer. The molar ratio of SiO2 / Al2O3 in the fluorescence analysis was 1.58. The adsorption capacity of saturated sodium chloride water vapor at 35℃ was 27.7%, and the calcium ion exchange capacity was 323 mg / g.

[0072] Comparative Example 1 According to the feed formula, the molar ratio of SiO2 / Al2O3 is 2.0, the molar ratio of Na2O / SiO2 is 1.4, and the molar ratio of H2O / Al2O3 is 160. Sodium aluminate solution and water glass solution are measured and added to the synthesis tank under stirring to form a slurry and gel, thus obtaining the first slurry. The gelation temperature is set at 50℃, and the mixture is stirred for 40 minutes. After stirring is stopped, static aging is carried out at 50℃ for 30 minutes. Stirring is then turned on, and a directing agent is added at 0.01% of the volume of the first slurry. High-temperature steam is introduced to raise the temperature for the first stage of crystallization at 80℃ for 3 hours. High-temperature steam is introduced again to raise the temperature for the second stage of crystallization at 95℃ for 3 hours, thus obtaining the second slurry. The second slurry is then subjected to solid-liquid separation, washing, and drying to obtain 4A zeolite.

[0073] The particle size D50 of the 4A zeolite was measured to be 3.578 μm by a laser particle size analyzer. The molar ratio of SiO2 / Al2O3 in the fluorescence analysis was 1.98. The adsorption capacity of saturated sodium chloride water vapor at 35℃ was 27.1%, and the calcium ion exchange capacity was 305 mg / g.

[0074] Comparative Example 2 According to the feed formula, the molar ratio of SiO2 / Al2O3 is 2.05, the molar ratio of Na2O / SiO2 is 1.3, and the molar ratio of H2O / Al2O3 is 144. Sodium aluminate solution and water glass solution are measured and added to the synthesis tank under stirring to form a slurry and gel, thus obtaining the first slurry. The gelation temperature is set at 45℃, and the mixture is stirred for 50 minutes. Stirring is then stopped for static aging at 45℃ for 30 minutes. Stirring is then turned on again, and a guiding agent is added at 0.001% of the volume of the first slurry. High-temperature steam is introduced to raise the temperature for the first stage of crystallization at 70℃ for 4 hours. High-temperature steam is introduced again to raise the temperature for the second stage of crystallization at 98℃ for 3 hours, thus obtaining the second slurry. The second slurry is then subjected to solid-liquid separation, washing, and drying to obtain 4A zeolite.

[0075] The particle size D50 of the 4A zeolite was measured to be 3.287 μm by a laser particle size analyzer. The molar ratio of SiO2 / Al2O3 in the fluorescence analysis was 2.01. The water vapor adsorption capacity of saturated sodium chloride at 35℃ was 26.7%, and the calcium ion exchange capacity was 298 mg / g.

[0076] The comparisons of the above examples and comparative examples show that using an aluminum excess gel system with a SiO2 / Al2O3 molar ratio of less than 2, and appropriately increasing the alkalinity of the system, yields 4A zeolite with better calcium ion exchange capacity and static water adsorption capacity. Controlling the SiO2 / Al2O3 molar ratio to 1.5~1.9 and the Na2O / SiO2 molar ratio to 1.5~2.0 can further improve the calcium ion exchange capacity and static water adsorption capacity of 4A zeolite. The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

[0077] Although preferred embodiments have been described in this specification, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this specification.

[0078] Obviously, those skilled in the art can make various modifications and variations to this specification without departing from its spirit and scope. Therefore, if such modifications and variations fall within the scope of the claims and their equivalents, this specification is also intended to include such modifications and variations.

Claims

1. A method for preparing 4A zeolite, characterized in that, Includes the following steps: Sodium aluminate solution and water glass solution are slurried and gelled to obtain the first slurry; The first slurry was subjected to static aging and segmented crystallization in sequence to obtain the second slurry; The second slurry was subjected to solid-liquid separation, washing, and drying in sequence to obtain the 4A zeolite; In the first slurry, the molar ratio of SiO2 to Al2O3 is 1.5 to 1.9, the molar ratio of Na2O to SiO2 is 1.5 to 2.0, and the molar ratio of H2O to Al2O3 is 120 to 180.

2. The preparation method according to claim 1, characterized in that, The sodium aluminate solution contains Al₂O₃ at a mass concentration of 35 g / L to 50 g / L; and / or, The caustic ratio αk of the sodium aluminate solution is 1.4 to 1.

6.

3. The preparation method according to claim 1, characterized in that, The mass concentration of SiO2 in the water glass solution is 360 g / L to 378 g / L; and / or, The water glass modulus M of the water glass solution is 3.0 to 3.

1.

4. The preparation method according to claim 1, characterized in that, The temperature for pulping and gelling is 35℃~55℃, and the time for pulping and gelling is 30min~60min.

5. The preparation method according to claim 1, characterized in that, The static aging temperature is 35℃~55℃, and the static aging time is 30min~90min.

6. The preparation method according to claim 1, characterized in that, The segmented crystallization includes: A guiding agent is added to the first slurry after static aging to carry out the first crystallization, and an initial crystallized slurry is obtained. The initial crystallized slurry is subjected to a second crystallization to obtain a second slurry.

7. The preparation method according to claim 6, characterized in that, The amount of the guiding agent added is 0.001% to 0.01% of the volume of the first slurry; and / or, The first crystallization temperature is 65℃~80℃, and the first crystallization time is 3h~6h; and / or, The second crystallization temperature is 92℃~98℃, and the second crystallization time is 2h~5h.

8. The method according to claim 1, characterized in that, The washing step is performed until the pH of the final filtrate is 10-11.

9. A 4A zeolite, wherein the 4A zeolite is prepared by the preparation method according to any one of claims 1 to 8.

10. The 4A zeolite according to claim 9, characterized in that, The 4A zeolite satisfies at least one of the following properties (1) to (4): (1) The particle size D50 of the 4A zeolite is 2μm to 5μm; (2) The calcium ion exchange capacity of the 4A zeolite is ≥310mg / g; (3) The static water adsorption capacity of the 4A zeolite is ≥ 27.5%; (4) The molar ratio of SiO2 to Al2O3 in the 4A zeolite is 1.50 to 1.90.